The Effects Of Parameter Variation In Open-Loop And Closed-Loop Control Scheme For An Electro-Hydraulic Actuator System - Rozaimi, Ghazali (Science and Engineering Research Support Society, 2016)
It is well known that the EHA system is exposed to the disturbances,uncertainties,and parameter variations which are caused by the changes in operating conditions for instance,total moving mass,supply pressure,servo-valve gain,bulk modulus,leakage coefficient,and friction.These problems pose to a great challenge in modelling and controller development for an EHA system.Degradation of the desired performance can be imposed if an improper control strategy is utilized.This paper discusses the fundamental study on the significant effect that leads to degradation of EHA system performance due to variation in the system parameters.A nonlinear EHA system model is developed and implemented in the simulation studies in open-loop and closed-loop control configuration.The finding shows that the servovalve gain resulted the most influential parameters to the EHA system performance as compared to the total moving mass and supply pressure parameters.In order to overcome these issues,the utilized controller should be robust enough to overcome the entire operating range that against such disturbances,uncertainties,and parameter variations.Therefore,a nonlinear and the intelligent control approach may be necessary to be designed in order to overcome these difficulties.